Application of magnetic biochar derived from food waste in heterogeneous sono-Fenton-like process for removal of organic dyes from aqueous solution - Chu, Jae Hun; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Journal of Water Process Engineering, 2020)
Biochar is a promising heterogeneous catalyst for wastewater treatment, and its efficiency can be improved via modification with iron oxide. We used food waste as a raw material for the preparation of magnetic biochar (MC), and the MC containing maghemite was successfully prepared via a pre-pyrolysis process. The MC was used as a catalyst for heterogeneous Fenton-like processes to remove organic dyes from water, and the synergistic effects of ultrasound (US) were evaluated. The heterogeneous sono-Fenton-like triple (US–H2O2–catalyst) system exhibited a high dye-removal efficiency. The calculated synergy factors were 5.73 for methylene blue (MB) and 10.95 for methyl orange (MO). The dye-removal efficiency increased with the H2O2 concentration, catalyst dose, and ultrasonic power. When the catalyst was reused five times, the removal efficiency for MB was maintained above 84 %, whereas that for MO was reduced to 10 %. The removal efficiency was also evaluated in real textile wastewater.
Keywords: Food waste; Heterogenous Fenton; Magnetic biochar; textile wastewater; Ultrasound